Electrodiagnostic Testing and Treatment for Carpal Tunnel Syndrome in Canada. (23rd November 2015) - Li Pi Shan, Rodney; Nicolle, Michael; Chan, Ming; Ashworth, Nigel; White, Chris; Winston, Paul; Dukelow, Sean
Abstract: Objectives: 1) Assess which electrodiagnostic studies Canadian clinicians use to aid in the diagnosis of carpal tunnel syndrome (CTS). 2) Assess whether Canadian clinicians follow the American Association of Neuromuscular & Electrodiagnostic Medicine/American Academy of Neurology/American Academy of Physical Medicine and Rehabilitation Practice Parameter for Electrodiagnostic Studies in CTS. 3) Assess how Canadian clinicians manage CTS once a diagnosis has been established. Methods: In this prospective observational study, an electronic survey was sent to all members of the Canadian Neuromuscular Group (CNMG) and the Canadian Association of Physical Medicine and Rehabilitation (CAPM&R) Neuromuscular Special Interest Group. Questions addressed which electrodiagnostic tests were being routinely used for the diagnosis of carpal tunnel syndrome. Management recommendations for CTS was also explored. Results: Of the 70 individuals who completed the survey, fourteen different nerve conduction study techniques were reported. Overall, 36/70 (51%) of participants followed the AANEM/AAN/AAPM&R Practice Parameter. The standard followed by the fewest of our respondents with 64% compliance (45/70) was the use of a standard distance of 13 to 14 cm with respect to the median sensory nerve conduction study. Regarding management, 99% would recommend splinting in the case of mild CTS. In moderate CTS, splinting was recommended by 91% of clinicians and 68% would also consider referral for surgery. In severe CTS, most recommended surgery (93%). Conclusions: There is considerable variability in terms of which electrodiagnostic tests Canadian clinicians perform for CTS. Canadian clinicians are encouraged to adhere to the AANEM/AAN/AAPM&R Practice Parameter for Electrodiagnostic Studies in CTS. RÉSUMÉ: Électrodiagnostic et traitement du syndrome du canal carpien au Canada. Objectifs : 1) Évaluer quelles études électrodiagnostiques sont utilisées par les cliniciens canadiens pour diagnostiquer le syndrome du canal carpien (SCC); 2) Évaluer si les cliniciens canadiens suivent les guides de pratiques de l'American Association of Neuromuscular & Electrodiagnostic Medicine/American Academy of Neurology/American Academy of Physical Medicine and Rehabilitation Practice Parameter for Electrodiagnostic Studies (AANEM/AAN/AAPM&R) concernant le SCC; 3) Évaluer comment les cliniciens canadiens traitent le SCC lorsque le diagnostic est posé. Méthode: Il s'agit d'une étude observationnelle prospective effectuée au moyen d'une enquête électronique auprès de tous les membres du Réseau canadien sur les maladies neuromusculaires (RCMN) et du groupe d'intérêt particulier de l'Association canadienne de médecine physique et de réadaptation (ACMP&R). Les questions portaient sur les tests électrodiagnostiques utilisés couramment pour poser le diagnostic de SCC. Les recommandations de traitement du SCC ont également été examinées. Résultats: Soixante-dix individus ont complété le questionnaire et ont rapporté l'utilisation de quatorze techniques différentes d'étude de la conduction nerveuse. En tout, 36 des participants (51%) suivaient les recommandations de pratique de l'AANEM/AAN/AAPM&R. L'utilisation d'une distance standard de 13 à 14 cm pour l'étude de la conduction sensitive au niveau du nerf médian était suivie par le plus petit nombre de nos répondants, soit 64% (45/70) qui rapportaient se conformer à ce standard. En ce qui concerne le traitement, 99% recommanderaient le port d'une attelle dans les cas de SCC léger. Chez les cas de SCC modéré, l'attelle était recommandée par 91% des cliniciens et 68% considéraient également référer le patient en chirurgie. Dans les cas de SCC sévère, la plupart recommandaient la chirurgie (93%). Conclusions: Chez les cliniciens canadiens, il existe une variabilité considérable quant à l'électrodiagnostic du SCC. Les cliniciens canadiens sont encouragés à adhérer aux paramètres de pratique concernant électrodiagnostic du SCC émis par l'AANEM/AAN/AAPM&R.